Unveiling a promising active host material for sodium metal anodes through V2AlC max derivation - Wasnik, Kundan; Patrike, Apurva; Shelke, Manjusha V. (ACS Applied Energy Materials, 2024)
To address the issue of nonuniform sodium deposition, in this study, V2ZnC (named VZC), which is synthesized by substituting Zn for Al in V2AlC, is used as a host material to facilitate effective Na utilization. The key concept is to utilize Zn and its forms as an active site to trap Na, while the high mechanical strength of VZC can accommodate volume changes in the sodium metal anode during charging and discharging. VZC displayed regulated plating and stripping at a higher current and capacity of 8 mA cm-2 and 2 mAh cm(-2), respectively, with Coulombic efficiency close to 99.99%.
Keywords: electrodes; Nucleation; overpotential; sodium metal; XPS depth profiling

Unlocking enhanced redox dynamics: the power of a bifunctional catalytic zinc phosphide interface in full cell and pouch lithium-sulfur batteries - Das, Anoushka K.; Yadav, Poonam; Verma, Tushar S.; Marulasiddappa, Thripuranthaka; Krishnamurty, Sailaja; Shelke, Manjusha V. (ACS Applied Materials & Interfaces, 2025)
Lithium-sulfur (Li-S) batteries face significant challenges, such as polysulfide dissolution, sluggish reaction kinetics, and lithium anode corrosion, hindering their practical application. Herein, we report a highly effective approach using a zinc phosphide (ZnP2) bifunctional catalyst to address these issues. The ZnP2 catalyst effectively anchors lithium polysulfides (LiPSs), catalytically reactivates them, and enhances lithium-ion diffusion. Utilizing a ZnP2-modified separator in a Li-S half-cell achieves an impressive initial capacity of 1145.4 mAh g-1, retaining 954 mAh g-1 and 99.8% Coulombic efficiency after 100 cycles, compared to the pristine separator. The underlying reaction mechanisms are thoroughly investigated through post-mortem analyses and density functional theory (DFT) calculations. Moreover, a Li-S full cell with an E/S ratio of 10 mu L mg-1 demonstrates stable cycling performance, achieving an initial capacity of 797.5 and 534 mAh g-1 after 100 cycles at 0.1C, with a negative-to-positive mass ratio of 3:1. Additionally, the real-world feasibility of lightweight and flexible Li-S pouch batteries with ZnP2-modified separators is explored, showing a stable performance over 100 cycles at 0.1C with 80% capacity retention. This engineered separator can be integrated with advanced sulfur cathodes to create high-energy-density, stable Li-S batteries for commercial applications.
Keywords: catalytic interlayer; full cell; lithium dendrite; lithium sulfur battery; polysulfide shuttling; pouchcell